Cognitive-behavioral therapy on psychological stress and quality of life in subjects with pulmonary tuberculosis: a community-based cluster randomized controlled trial - Zuo, Xiaowei; Dong, Zongmei; Zhang, Peng; Zhang, Pan; Zhu, Xianghua; Qiao, Cheng; Yang, Yongjie; Lou, Peian (BMC public health, 2022)
Background Anxiety and depression are two common psychological disorders in patients with pulmonary tuberculosis. We aimed to explore the effects of cognitive-behavioral therapy (CBT) on psychological stress and quality of life in patients with pulmonary tuberculosis. Methods From September 2018 to November 2018, 20 communities (461 participants in total) were randomly assigned in an intervention or control group following a two-level cluster random design. The intervention group underwent CBT for 2 months, whereas the control group received routine follow-up. Anxiety, depression, and quality of life were assessed using the Patient Health Questionnaire-9 (PHQ-9), General Anxiety Disorder questionnaire (GAD-7), and 36-Item Short-Form Health Survey (SF-36) scales, respectively. Comparisons between the two groups were conducted using independent samples t-tests, and differences between the two groups before and after treatment were analyzed using paired samples t-tests. Results There were a total of 454 participants in the final analysis. After 2 months of CBT intervention, the CBT group had a GAD-7 score that was 1.72 lower than the control group (1.47-1.99, p < 0.001), a PHQ-9 score of the CBT group that was 2.05 lower than that of the control group (1.74-2.37, p < 0.001). The CBT group had a total SF-36 score that was 10.7 lower than that of the control group (95% CI: 7.9-13.5, p < 0.001). In patients with different degrees of anxiety and depression, only those in the intervention group who had mild and moderate anxiety and depression symptoms showed a significant reduction in anxiety and depression scores following the intervention. Conclusions CBT can relieve anxiety, and depression symptoms and increase the quality of life in subjects with pulmonary tuberculosis. Trials registration ChiCTR-TRC-12001958 Date of Registration: 22/02/2012. Keywords: Cognitive-behavioral therapy, Pulmonary tuberculosis, Anxiety, Depression, Quality of life